A Analisis Kesesuaian Lahan Dan Daya Dukung Wisata Pantai Tawang, Kabupaten Pacitan - Handayani, Muliawati (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
Tawang Beach has potency as a tourism destination in Pacitan District, East Java. Unique type of beach and the existence of Fish Auction are tourist attractions available on the beach. JLS and technological developments have contributed to the increase in the number of tourist visits. Studies on the suitability and carrying capacity of the environment in Tawang Beach as beach tourism are important to support development and proper management. Assessment of suitability area uses quantitative assessment instruments, based on parameters of water depth, beach type, beach width, substrat material, current velocity, slope, brightness, coastal land cover, dangerous organism, and availability of fresh water. Analysis of the carrying capacity of the area uses calculations according to the area of Tawang Beach and the range time visitors enjoying the beach. The results of the analysis show that Tawang Beach is suitable (S1) to be developed as a beach tourism area with a value of 80-84.16%. The total carrying capacity of the area is 205 people/day